AB0515 Spanish society of rheumatology (SER) recommendations on primary antiphospholipid syndrome (APS). in a patient with obstetric aps, which treatments are more effective? systematic review. (12th June 2018) - Sánchez Pérez, H.; Nishishinya Aquino, M.; Pereda, C.; Díaz del Campo Fontecha, P.; Martínez Zamora, M.
Abstract : Background: Pregnancy complications and poor obstetric prognosis are part of the manifestations of APS. The obstetric APS (O-APS) includes 3 or more early miscarriages, 1 or more intrauterine foetal deaths, prematurity secondary to preeclampsia or placental insufficiency, intrauterine growth retardation and HELLP syndrome among others. There is disagreement among different published studies regarding the need of preconceptional or primary thromboprophylaxis (treating with anticoagulant/antiaggregant drugs in the presence of specific autoantibodies but without previous clinical events) and the most effective and safest drug to use, as well as which treatment should be chosen in the case of secondary thromboprophylaxis (treating in the presence of autoantibodies and recurrent miscarriages or previous obstetric complications). Objectives: To evaluate the available scientific evidence on which treatments are the most effective and safest in O-APS. Methods: A systematic review (SR) was performed to evaluate the efficacy and safety of different interventions (Aspirin (ASA), Heparin, Antimalarials, Immunoglobulin IV (IVIG), others) in pregnant women with O-APS. We included SR, randomised clinical trials (RCTs) and comparative cohort studies. Result measures on morbidity (prematurity, low birth weight, need for intensive care, impaired cognitive development, preeclampsia, eclampsia, HELLP, abruptio placentae) and mortality included both the newborn and the pregnant woman. A peer review selection and analysis of the studies was carried out (SP, H; NA, MB). Results: 788 citations were identified (Medline, EMBASE, CENTRAL. May 2017). We included 17 studies: 5 SR, 5 RCTs and 7 cohort studies. Results are shown on the table 1 below: Conclusions: In women with O-APS: Secondary thromboprophylaxis: The combination of ASA +Heparin is more effective than ASA monotherapy. With regards to the use of IVIG, corticosteroids and statins: NO representative conclusions can be drawn from published studies Pre-conceptional thromboprophylaxis, primary thromboprophylaxis: NO representative conclusions can be drawn from published studies. Acknowledgements: This review is part of the preparation of SER Recommendations on Primary APS treatment. Disclosure of Interest: None declared